Effect of intradialytic exercise training on hemodialysis-induced myocardial stunning: a pilot-controlled trial - Josse, Matthieu; Patrier, Laure; Cristol, Jean-Paul; Isnard, Myriam; Grandperrin, Antoine; Turc-Baron, Cécile; Nottin, Stéphane; Mandigout, Stéphane; Maufrais, Claire; Obert, Philippe (Clinical kidney journal, 2025)
Hemodialysis (HD) can lead to left ventricular (LV) transient regional wall motion abnormalities (RWMAs), due to segmental hypoperfusion, better known as myocardial stunning. Repeated episodes of HD-induced ischemia contribute directly to the development of heart failure and increased mortality in patients receiving HD. Intradialytic exercise (IDE) training is capable of exerting favorable effects on the cardiovascular system. However, its impact on HD-induced myocardial stunning remains currently unknown. In this prospective controlled study, 31 patients participating in an intradialytic aerobic and resistance training program (3/week for 16 weeks) were compared with 30 patients receiving usual care. Two-dimensional echocardiography was performed at baseline and follow-up both just before HD onset (T ) and at peak stress of HD (T ). LV longitudinal strain from an 18-segment model were used to assess the presence of RWMAs. Training resulted in a significant reduction of RWMAs at T between groups [-2.22 segments; 95% confidence interval (CI) -0.49/-3.96; = .01]. Compared with usual care, trained patients demonstrated also a greater reduction in the decline of global longitudinal strain during HD (-1.45%; 95% CI -0.24/-2.66; = .01). There were significant reductions in LV mass (-23.3 g; 95% CI -8.7/-37.9; = .002) and improvements in LV ejection fraction (4%; 95% CI 1.5/6.6; = .002) between groups favoring IDE. Correlations were found between change in RWMAs with change in LV mass and ejection fraction over the study period. IDE training is cardioprotective, improving LV remodeling and reducing HD-induced myocardial stunning.